Thermochemical sulfate reduction in fossil Ordovician deposits of the Majiang area: Evidence from a molecular-marker investigation - Wang, Guangli; Li, N.; Gao, B.; Li, X.; Shi, S.; Wang, T. (Science in China Press/Zhongguo Kexue Zazhishe, 2013)
The main reservoirs of Majiang fossil deposits consist of the Silurian Wengxiang group, dominantly sandstones, and the Ordovician Honghuayuan formation, dominantly carbonate rocks, and the Lower Cambrian Niutitang Formation mudstones serve as the major source rocks. Thermochemical sulfate reduction (TSR) might have taken place in the Paleozoic marine carbonate oil pools, as indicated by high concentrations of dibenzothiophenes in the extracts (MDBT=0.27-4.32 µg/g extract, and MDBT/MPH= 0.71-1.38). Hydrocarbons in the Pojiaozhai Ordovician carbonate reservoirs have undergone severe TSR and are characterized by higher quantities of diamondoids and MDBT and heavier isotopic values (δ13C=-28.4‰). The very large amounts of dibenzothiophenes might be products of reactions between biphenyls and sulfur species associated with TSR.